A different manner to share a house: is a colonial species possible in Ceriantharia (Cnidaria; Anthozoa)? - Ceriello, Hellen [UNESP]; Lopes, Celine S. S. [UNESP]; Dias, Gustavo Muniz; Stampar, Sérgio N. [UNESP] (Springer Nature, 2019)
Ceriantharians or tube-dwelling sea anemones are known for synthesizing soft and flexible tubes made of mucus, cnidae filaments (ptychocysts), and sediments found on the soft bottom. These tubes are used to house and protect them from danger, although many species of marine invertebrates use ceriantharian tubes as alternative substrates. Little is known about the organizational structure of ceriantharians in their own tubes. Although ceriantharians are always considered solitary animals, this study presents the first record of a ceriantharian colony of Botrucnidifer norvegicus Carlgren, 1912. Future studies regarding the population structure in ceriantharian aggregations may help to clarify this unusual habit for Ceriantharia.
Keywords: Assemblages; Colonialism; Population structure; Tube-dwelling anemones